The need of Palliative care model in cancer patients in India-A long overdue - Kaushal, Kanica; Bhattacharya, Sudip; Singh, Amarjeet (Indian Journal of Community Health, 2018)
WHO defined palliative care as “an approach that improves the quality of life of patients and their families facing the problems associated with life-threatening illness, through the prevention and relief of suffering by means of early identification and impeccable assessment and treatment of pain and other problems, physical, psychosocial, and spiritual.” (1) The concept of palliative care was introduced in the mid-1980s in India. McDermott E et al found Kerala to have 83 palliative care services as against 139 in the whole of the country in 2008. (2) The community palliative care projects of northern Kerala and the Neighborhood Network in Palliative Care (NNPC) is a solution to achieve meaningful coverage and care for the terminally ill. They demonstrate the way to "Palliative Care for All". (3)